1996
DOI: 10.3171/jns.1996.85.6.1184
|View full text |Cite
|
Sign up to set email alerts
|

Transillumination in minimally invasive surgery for carpal tunnel release

Abstract: An alternative technique for performing minimally invasive release of carpal tunnel syndrome is described. The suggested methodology is based on transillumination of the carpal tunnel during surgery. The advantages of the technique are discussed and compared with other available surgical procedures including endoscopy. The authors also describe preliminary operative results in 50 consecutive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Late complications, on the other hand, have a relatively high incidence. These are hypertrophic scar formation, scar tenderness, pillar pain, loss of grip strength and sympathetic dystrophy resulting in the delay of returning to daily activities or work and emotional distress (2,5,6,14). To reduce these complications, various limited incisions or endoscopic techniques are described by authors (3,8,10,12,19,23,24,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late complications, on the other hand, have a relatively high incidence. These are hypertrophic scar formation, scar tenderness, pillar pain, loss of grip strength and sympathetic dystrophy resulting in the delay of returning to daily activities or work and emotional distress (2,5,6,14). To reduce these complications, various limited incisions or endoscopic techniques are described by authors (3,8,10,12,19,23,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, Franzini et al reported a minimally invasive technique with a small longitudinal incision of 1 cm., proximal to the wrist crease. They performed 473 operations by using that incision and transillumination technique with 90 % complete remission (14). In this study, we aimed to analyze the outcome of patients operated for carpal tunnel syndrome using microsurgical limited uni skin incision.…”
Section: Discussionmentioning
confidence: 99%
“…However, late complications have a relatively high incidence. These are hypertrophic scar formation, scar tenderness, pillar pain, loss of grip strength and sympathetic dystrophy resulting in the delay of returning to daily activities or work and emotional distress 4,8,9,28 . As many as 24% of post-operative problems in median nerve release is related to skin incision 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Several other methods of imaging the region of the carpal tunnel, including ultrasound and thermography, 22,44,67,113,165 have been evaluated. Although ultrasound has been found to be 95% accurate diagnostically, 22 with 90% EMG correlation, 113 and is excellent in judging postoperative release at follow-up, it is still inferior to MRI in assessing mild CTS and determining alternative etiologies for the underlying nerve compression.…”
Section: Median Nerve Entrapment At the Wristmentioning
confidence: 99%